Answer:
The sum of f(2) and g(-3) is -7.
Step-by-step explanation:
f(x) = 3x - 2
f(2) = 3(2)-2
f(2) = 6 -2 = 4
g(x) = 4x + 1
g(-3) = 4(-3) +1
g(-3) = -12 + 1 = -11
f(2) + g(-3) = 4 + (-11)
f(2) + g(-3) = -7
Answer:
38km
Step-by-step explanation:
pa brainlest na lang po ty po
First, let's fine the decimal of each fraction.
-5 Divided By 6 = -0.83333333333
17 Divided By 18 = 0.94444444444
-2 Divided By 9 = -0.22222222222
-5/6 - 17/18 - (-2/9) = -1.55555555556
Answer:
the answer is C
Step-by-step explanation:
Because no one cares and your question makes no sense.
Answer:
i think that is 4
Step-by-step explanation:
fydxudugxxfjg